Investigation of wrapped effects on bow‐tie antenna with and without resistive loading for pulsed radar applications. Issue 1 (1st January 2019) - Lee, D.; Melek, W.; Shaker, G.
Abstract : The effects of the wrapped bow‐tie antenna with and without resistive loading are explored for pulsed radar applications. The antenna characteristics such as voltage standing wave ratio, input impedance, reflected pulse of the antennas and radiated electric field are investigated by fully wrapping the planar bow‐tie antenna. The antenna characteristics of the loaded antennas are shown to be robust with respect to the deformation of the planar bow‐tie antenna. The peak‐to‐peak antenna reflected voltages of the conventional bow‐tie planar antenna (PA) and bow‐tie wrapped antenna (WA) are 0.24 and 0.49 V, respectively, whereas those of the resistor‐loaded PA (RPA) and the resistor‐loaded WA (RWA) are 0.23 and 0.25 V, respectively. The calculated figure of merit of the PA and WA are −4.58 and −7.92 dB, respectively, whereas those of the RPA and RWA are −20 and −18.42 dB, respectively. On the basis of the performance evaluation, the pulse radiating performance of the resistively loaded antennas is shown to be stable with respect to the deformation of the planar bow‐tie antenna.